EFFECT OF MANGOSTEEN PEEL EXTRACT (Garcinia mangosteen) TO FIBROBLAST NUMBER AS PERIODONTAL DISEASE THERAPY - Adisty Restu Poetri; Rosa Pratiwi; Adhiatarika Rismadanti (Denta Journal Kedokteran Gigi, 2023)
Background: In Indonesia, periodontitis is among the most prevalent periodontal disease. The dentist may administer extra adjunctive therapy as a gel to treat inflammation and the bacterium that causes periodontitis. The antibacterial and anti-inflammatory xanthones included in mangosteen peel extract gel speed up the inflammatory phase. Objective: This study aimed to determine the effectiveness of mangosteen peel extract gel in increasing the number of fibroblast cells in the healing process of periodontitis in Wistar rats (Rattus norvegicus). Material and Method: This research was an experimental laboratory design with a post-test-only design divided into four groups, 50% mangosteen peel extract gel group, 75% mangosteen peel extract gel group, metronidazole gel group, and metronidazole plus gel group. Result: The research data were analyzed using the One Way ANOVA test and showed a significant value difference with a p=0.000 (p<0.05). However, in the inter-group test with Bonferroni post hoc, it was found that there was no significant difference between the 75% mangosteen peel extract gel group and the metronidazole gel group with a value of p = 0.709 (p>0.05). Conclusion: This study concludes that mangosteen peel extract gel effectively increases fibroblast cells' number in the periodontitis healing process.